Objektivitas Majelis Pengawas Daerah Dalam Melaksanakan Pengawasan Terhadap Notaris - Andi Maulana; Ngadino Ngadino (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractThe Supervisory Council has the authority to supervise and provide guidance to Notaries. The supervision carried out by the Notary Public often raises doubts about the existence of a Conflict of Interest in supervision. The problem examined in this study is to analyze the implementation of MPD duties from the Notary element in supervising the Notary in Semarang City and the Semarang City MPD from the Notary element in carrying out the supervision of the Notary. The method used in this research is the socio-legal approach method with analytical descriptive research specifications. The results of this study are 1) The Semarang City Regional Supervisory Council from the Notary element in carrying out supervision of Notaries is very important, because in this case, the Supervisory Council of Notary Public must have better knowledge and experience in the Notary profession. 2) Many parties have doubts about the objectivity of the Supervisory Council, especially those originating from the Notary element. This is because a Notary who is a member of the Supervisory Council is a Notary who is currently active as a Notary, so this raises doubts.Keywords: regional supervisory council; supervisors; notaryAbstrakMajelis Pengawas memiliki kekuasaan guna mengawasi serta membina Notaris. Pengawasan yang dilaksanakan oleh Unsur Notaris sering mengakibatkan rasa ragu terhadap munculnya Konflik Kepentingan pada pengawasan. Masalah yang diteliti pada penelitian ini yaitu menganalisis pelaksanaan tugas MPD dari unsur Notaris dalam mengawasi Notaris di Kota Semarang, dan MPD Kota Semarang dari unsur Notaris dalam mengawsasi Notaris. Penelitian ini memakai metode pendekatan socio-legal research berupa penelitian analisis deskriptif. Hasil dari penelitian ini ialah 1) Sangat penting bagi MPD Kota Semarang dari unsur Notaris untuk melakukan pengawasan terhadap Notaris dari sudut pandang notaris, sebab dalam hal ini Majelis Pengawas Dari Unsur Notaris wajib mempunyai pengetahuan yang luas serta pengalamannya sebagai Notaris. 2) Banyak pihak yang meragukan objektifitas dari Majelis Pengawas, terutama yang asalnya dari unsur Notaris. Pasalnya, Notaris yang menjadi anggota Majelis Pengawas merupakan Notaris yang saat ini aktif sebagai Notaris, sehingga menimbulkan keraguan.Kata kunci: majelis pengawas daerah; pengawas; notaris